Learning Obstacles in Nahwu Learning: A Study on the Theory of Didactic Situations for Islamic Boarding School Students - Syirojul Huda; Aji Rizqi Ramadhan; Arina Dienana; Yusta Rizaldi Yusuf Suliadi (Prodi Pendidikan Bahasa Arab, Universitas Muhammadiyah Tangerang, 2026)
This study aims to analyze several types of learning obstacles faced by junior high school students in learning Nahwu, focusing on the topic of mubtada' and khobar. This study uses a descriptive qualitative method with the Theory of Didactic Situations (TDS) approach. The study was conducted at the At-Tarbiyah Sukabumi Islamic Boarding School with a sample of 20 ninth-grade students who had studied Nahwu, specifically the chapters on mubtada' and khobar. Data were collected through written tests, in-depth interviews, and an analysis of textbooks. The findings indicate that students face epistemological, didactic, and ontogenetic barriers. Epistemological barriers are the most dominant, as evidenced by students' difficulties in applying theoretical knowledge to practical examples and understanding changes in the mubtada'-khobar structure. Didactic barriers arise due to ineffective teaching methods, while ontogenetic obstacles are related to students' mental readiness. This study will contribute to theoretical discussions on learning obstacles and the theory of didactic situations in language learning. Further research is needed to develop learning trajectories to help students overcome several learning obstacles.